Caracterisation Des Pratiques Agroforestieres A Base De Cacaoyers En Zone De Foret Dense Semi- Decidue : Cas De La Localite De Lakota (Centre- Ouest, Cote d’Ivoire) - Abdoulaye, Cisse; Kouadio, Aka Jean Claude; Djaha, Kouame; Aimé, Vroh Bi Tra; Yves, Adou Yao Constant; Edouard, N’guessan Kouakou (European Scientific Journal, ESJ, 2016)
In the area of Lakota (Midwest, Côte d’Ivoire), where the vegetation is a semi-deciduous forest, cacao growing is practiced by people from different origins. Cacao cropping techniques seem to be influenced by some social and cultural habits, according to the people and the agroecological areas. The present study aimed to understand(1) the cacao cropping systems and to identify(2) the reasons underlying the choice of vegetal species combined to cacao trees in these rural communities. To achieve this goal, interviews were realised with cacao farmers of four villages of the area. These interviews concern farmers’ profiles, the former agriculture practices, the variety of the cultivated cacao and the plants combined to cacao trees. The results show that among the 223 interviewed farmers, 72 (32.3% of the farmers) are natives, 42 (18.8% of the farmers) are immigrants and 109 (48.9% of the farmers) are non-native Ivorians. In total, 77 species regularly combined to cacao trees were named by the farmers and they can be divided into local species and exotic species. Plots ordination shows three agroforestry systems according to ethnic group of the locality. Cacao farms with the large proportion of local species are owned by Lakota native people "Dida". The exotic species are dominant in cacao farms that belong to immigrants (Malian, Burkina Faso and Guinean people) and "Malinké" people (a non-native ivorian ethnic group). The Akan people (a non-native ivorian ethnic group) combine in a same proportions exotic and local species in their cacao farms.